PENGARUH LINGKUNGAN KERJA NON FISIK, BEBAN KERJA DAN LEADER MEMBER EXCHANGE (LMX) TERHADAP KINERJA KARYAWAN PT. PEGADAIAN AREA AMBON - Lilipaly, Yustitia Rengga; Pentury, Gerrits; Sijabat, Asiani (Jurnal Ilmiah Global Education, 2023)
The aim of this research is to analyze the influence of the non-physical work environment, workload and leader member exchange (LMX) on the performance of PT employees. Ambon Area Pawn Shop. The type of research used by researchers is quantitative research. Researchers collect data that can be measured using statistical, mathematical or computational techniques. The results show that the R Square value is 0.552 which means that 55.2% of employee performance is jointly influenced by the variables described in the model, while the rest is influenced by factors outside the model. Partially non-physical environmental variables, workload and leader member exchange on the performance of employees of PT. Pegadaian Area Ambon.